SISTEM INFORMASI PERSURATAN PADA DINAS SOSIAL PEMUDA DAN OLAH RAGA KOTA SEMARANG (Information Technology and Telematics, 2012)
Abstract Paperless work-culture system will be developed in the Social Service Youth and Sports of Semarang through implementation of information technology (IT) so that the administrative practice of mailing is loaded with manual verification can be replaced with electronic verification. It is noted in the collection of functions that are required to design and archival information systems mailing Social Service Youth and Sport mail archiving paradigm approach. From the results obtained that the understanding of the relationship between software that is designed with the external environment helps decide how the system should provide the required functionality and how to structure the system so it can communicate effectively with its environment Keywords Information systems, mailing